2001
DOI: 10.1207/s15327698jfc0104_02
|View full text |Cite
|
Sign up to set email alerts
|

Modernity and the Communicative Management of Multiple Roles: The Case of the Worker-Parent

Abstract: This study explores the relations among interpersonal communication, self-identity, and conditions of modernity in the context of work and parenting. The conceptualization of role construction as communicative process is an extension of the idea that social reality, which includes social and personal identity, is created through human interaction. Conditions of modernity intensify individuals' experience of self-identity as constructed rather than given, and heighten the constitutive function of interpersonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 17 publications
2
20
1
Order By: Relevance
“…First, participants expressed the independence they experienced and desired as tied to their perceptions and interpretations of the families and particularly the women around whom they grew up. Typically, they mentioned how they had been encouraged or found motivation to be independent and self-supporting from a young age, supporting other studies that have found that families of origin and particularly mothers have a large influence on women's work and family identity constructions (Golden 2001;Johnston et al 2008;Medved et al 2006). Many of them had seen negative consequences of women not having a sense of and the financial means to maintain their independence, and at least one participant had recently read Bennetts' (2007) book on the dangers of women lacking financial independence.…”
Section: Gendered Identity Negotiationssupporting
confidence: 75%
“…First, participants expressed the independence they experienced and desired as tied to their perceptions and interpretations of the families and particularly the women around whom they grew up. Typically, they mentioned how they had been encouraged or found motivation to be independent and self-supporting from a young age, supporting other studies that have found that families of origin and particularly mothers have a large influence on women's work and family identity constructions (Golden 2001;Johnston et al 2008;Medved et al 2006). Many of them had seen negative consequences of women not having a sense of and the financial means to maintain their independence, and at least one participant had recently read Bennetts' (2007) book on the dangers of women lacking financial independence.…”
Section: Gendered Identity Negotiationssupporting
confidence: 75%
“…Golden (2001) contended that the conditions of modernity, the rise in expert systems, the pluralization of our social worlds, and social learning through the mass media have made choosing a workermother identity more complex and stressful than ever before. The current cultural climate that pits mothers against mothers undermines all women and is not healthy for mothers or children.…”
Section: Discussionmentioning
confidence: 99%
“…The construction of identity, according to Berger and Luckmann (1966), involves both sociocultural influences and personal influences, such as the validation of others. Golden (2001), for example, noted the importance of affirmation of friends and family in the construction of workerparent identity. We know that social support in general has positive effects on psychological well-being (Van Willigen & Drentea, 2001), and lack of perceived support is associated with increased levels of stress and unhappiness (Deater-Deckard & Scarr, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Medved (2010) shows the prominence of the social construction of gendered identities as a frequent focus of work-life scholarship (see also Kirby & Buzzanell, 2014), and Golden (2001) asserts successful work-family management is as much an identity issue as it is a time management issue. Further, Wieland (2010Wieland ( , 2011 articulates identity construction as a normative activity through which socially acceptable ideals/ideologies of who one should be (i.e., how a good worker or a good mother should look, act, and feel) are woven into an individual's understanding of who s/he is.…”
Section: Two Juggling Mothersmentioning
confidence: 99%